Safflower Seed Oil, Containing Oleic Acid and Palmitic Acid, Enhances the Stemness of Cultured Embryonic Neural Stem Cells through Notch1 and Induces Neuronal Differentiation - Ghareghani, Majid; Zibara, Kazem; Azari, Hassan; Hejr, Hossein; Sadri, Farzad; Jannesar, Ramin; Ghalamfarsa, Ghasem; Delaviz, Hamdallah; Nouri, Ebrahim; Ghanbari, Amir (Frontiers in Neuroscience, 2017)
Embryonic neural stem cells (eNSCs) could differentiate into neurons, astrocytes and oligodendrocytes. This study was aimed to determine the effect of safflower seed oil, which contains linoleic acid (LA), oleic acid (OA) and palmitic acid (PA), on cultured eNSC proliferation and differentiation, in comparison to linoleic acid alone. Results showed that safflower seed oil, but not LA, increased significantly the viability and proliferation of eNSCs. Moreover, treatment of NSCs by safflower seed oil, but not LA, resulted in a significant increase in mRNA levels of notch1, hes1, and Ki-67, and protein levels of notch intracellular domain (NICD), in comparison to controls, indicating an enhancement of stemness. Finally, safflower seed oil, but not LA, caused an increase in the number of oligodendrocytes (MBP+), astrocytes (GFAP+) and neurons (β-III tubulin+) of which only the increase in β-III tubulin positive cells was statistically significant. In summary, OA and PA, present in safflower seed oil may prove beneficial for the enhancement of eNSCs and their neuronal differentiation.